ABSTRACT O1: Muslim Solidarity In Crisis - Mohamad Habibullah, Siti Noraida (International Journal of Human and Health Sciences (IJHHS), 2025)
Objectives: The policies on forced migrants in Malaysia have been frequently debated but lack sustainable solutions. Despite Islam being the country’s official religion, fundamental Islamic principles seem to have little influence on policies regarding forced migrants. This analysis examines the struggles faced by forced migrants in Malaysia, including limited access to healthcare, and explores the potential for Muslim solidarity to positively influence policies and support for them. It also explores the gap between the expected emphasis on Muslim Solidarity and its real-world application in Malaysia’s forced migrant policies. Methodology: This empirical qualitative study is based on semi- structured interviews with nine participants from three groups: Muslim politicians, Islamic scholars, and NGO advocates for forced migrants in Malaysia. These groups were chosen to explore their insights on migrant struggles, barriers to effective governance, and how Muslim solidarity may influence policies, societal acceptance, and healthcare access for forced migrants. Results: The findings highlight the everyday struggles of forced migrants, exacerbated by the absence of a legal framework and the need for clearer policies to provide protection and support, including access to healthcare. While Muslim solidarity is viewed as a potential influence on policymakers, its practical application faces significant limitations. These include a lack of unified political will, conflicting political agendas, the racialisation of forced migrants, and insufficient public and scholarly awareness. Islamic scholars are identified as key in raising public awareness and guiding decision-makers toward policies more aligned with Muslim solidarity. Participants also expressed shared frustration over the neglect of a basic Islamic principle when addressing the healthcare needs of forced migrants, especially the inability to work which further limits access to healthcare. Conclusion: The struggles of forced migrants can be alleviated by incorporating the concept of Muslim solidarity into policies while acknowledging its limitations. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S26